The Potential Role of Previous Physical Exercise Program to Reduce Seizure Susceptibility: A Systematic Review and Meta-Analysis of Animal Studies - Arida, Ricardo Mario; Passos, Adrielle Andrade; Graciani, Alexandre Lebedev; Brogin, João Angelo Ferres; Ribeiro, Mayara de Almeida Lima; Faber, Jean; Gutierre, Robson Campos; Teixeira-Machado, Lavinia (Frontiers in Neurology, 2021)
Background: Clinical and animal studies indicate a reduction in seizure frequency as well as decrease susceptibility to subsequently evoked seizures after physical exercise programs. In contrast to the influence of exercise after epilepsy has been established, various studies have been conducted attempting to investigate whether physical activity reduces brain susceptibility to seizures or prevents epilepsy. We report a systematic review and meta-analysis of different animal models that addressed the impact of previous physical exercise programs to reduce seizure susceptibility. Methods: The electronic search was performed in the MEDLINE (PubMed), Web of Science (WOS), Scopus, PsycINFO, Scientific Electronic Library Online (SciELO) databases, and grey literature, without restrictions in the year or language of publication, Results: Fifteen studies were included in the final analysis (543 animals), 13 of them used male animals, and the Wistar rats were the most common species used in the studies (355 animals). The chemoconvulsants used in the selected studies were pentylenetetrazol, penicillin, kainic acid, pilocarpine, and homocysteine. We assessed the impact of study design characteristics and reporting of mitigations to reduce the risk of bias. We calculated a standardized mean difference effect size for each comparison and performed a fixed-effect meta-analysis. The meta-analysis included behavioral analysis (latency to seizure onset, n= 6 and intensity of motor signals, n= 3) and electrophysiological analysis (spikes/min, n = 4, and amplitude, n= 6). The overall effect size observed in physical exercise compared to controls for latency to seizure onset was -3.99 [95% CI: -8.72, 0.74] (seconds) and the intensity of motor signals was -0.02 [95% CI: -0.17, 0.12] (on a scale from 0 to 5). The largest effects were observed in electrophysiological analysis for spikes -20.54 [95% CI: -25.20, -15.88] (spikes/min), and amplitude -154.45 [95% CI: -169.12, -139.79] (µV). Conclusion: In sum, the selected studies indicate that previous physical exercise program can reduce seizure susceptibility. The value of future studies could be enhanced by improving the reporting of methodological criteria, the clinical relevance of the models, and behavioral assessments. Nevertheless, the evidence supports the hypothesis that physical exercise reduces seizure susceptibility.